DEVELOPMENT OF TEXT MINING APPLICATION WITH ASSOCIATION RULE METHOD FOR DOCUMENTS SEARCHING - Kadek Indah Purnama Sari (Universitas Pendidikan Ganesha, 2012)
This study aimed in: (1) Designing Text Mining Applications With Association Rule Methods for Documents Searching. (2) Implementing Text Mining Applications With Association Rule Methods for Documents Searching. In the design and implementation, researcher was using Text Mining with Association Rule Analysis Method which has three stages: (1) Parsing Text, (2) Stopwording, (3) Stemming. The input of this application is Indonesian language text, whereas the output is searching result which are documents to be searched. The testing process used blacx box testing (functional) and the white box testing (conceptual / structural). The results of this research is the Text Mining Applications With Association Rule Methods for Documents Searching named “Text Miner”, which is implemented by using the Delphi 7 programming language. Based on trial results, it is known that the application